2012
DOI: 10.1002/adma.201104619
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Crystallization around Bends and Sharp Corners

Abstract: Control over the molecular orientation in organic thin films is demonstrated with precise in-plane spatial resolution over large areas. By exploiting the differential crystallization rates on substrates with different surface energies, the radial symmetry of spherulitic growth can be disrupted by preferentially selecting the molecular orientations that promote growth along the paths of the underlying patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 39 publications
7
103
0
Order By: Relevance
“…Whereas in the case of dendritic solidification of the many crystal orientations present initially only a single orientation survives in the meandering channel, leading to single-crystal freezing in the cast volume (Figure 29(a)), [28] due to GFN (an inherent interfacial property of this growth mode), polycrystalline growth propagates through the orientation selector, initiating spherulitic growth inside the cast volume ( Figure 29(b)). [111] Indeed, the latter prediction was confirmed by recent experiments on organic thin films [112] (Figure 29(c), (d)). The same boundary conditions can be used to define tubes for modeling the formation of polymeric shishkebab structures [113] on carbon nanotubes (Figure 30).…”
Section: Crystallization In Confined Domainssupporting
confidence: 59%
“…Whereas in the case of dendritic solidification of the many crystal orientations present initially only a single orientation survives in the meandering channel, leading to single-crystal freezing in the cast volume (Figure 29(a)), [28] due to GFN (an inherent interfacial property of this growth mode), polycrystalline growth propagates through the orientation selector, initiating spherulitic growth inside the cast volume ( Figure 29(b)). [111] Indeed, the latter prediction was confirmed by recent experiments on organic thin films [112] (Figure 29(c), (d)). The same boundary conditions can be used to define tubes for modeling the formation of polymeric shishkebab structures [113] on carbon nanotubes (Figure 30).…”
Section: Crystallization In Confined Domainssupporting
confidence: 59%
“…Therefore, it is possible that like the sublimed films, the nonannealed spin-cast films have low interface thermal resistances, smaller than that of the vapor annealed films. In fact, Lee et al 29 have suggested that the vapor annealing process causes dewetting of the films from the substrate, which should increase the interface thermal resistance.…”
Section: Resultsmentioning
confidence: 99%
“…12,13,29 To prepare these, TES-ADT was dissolved in toluene to form a 2 wt% solution, which was spin-coated on to the substrate at 1000 rpm. Then the sample was heated in air at 80 o C to remove residual solvent, yielding a ~ uniform thickness film.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…C Guided crystallization of solution-processed organic semiconductor thin films via substrate patterning can enable the control of material properties with fine spatial resolution and be used to preferentially orient molecules along a given direction. 1,2 Potential applications of guided crystallization on pre-specified templates include the fabrication of patterned optical coatings or conductive paths with arbitrary shapes 1 as well as dense arrays of organic thin-film transistors. 2 In addition, the ability to control the alignment of organic semiconductor small molecules has been employed to study the effect of grain boundary orientation mismatch on electrical properties.…”
mentioning
confidence: 99%